Aspek Hukum Pidana Warga Negara Asing Ke Negara Kesatuan Republik Indonesia Tanpa Melalui Pemeriksaan Pejabat Imigrasi (Studi Putusan No: 1474/Pid.Sus/2016/PN. Mdn) - Rama Sari Atiwiz Purba; Ridho Mubarak; Rafiqi Rafiqi (Universitas Medan Area, 2019)
Immigration is a form of legal action that is marked by the arrival or presence of foreigners in the territory of the Republic of Indonesia and the departure of Indonesian citizens to the territory of other countries by using or not having immigration travel documents. The method of this research is normative juridical, which is using Library Research. Legal arrangements regarding foreign nationals to Indonesia without going through immigration official inspection are outlined in Article 8 and Article 9 of Law No. 6 of 2011 concerning Immigration and also in Article 3, Article 20 and Article 21 of Government Regulation Number 31 of 2013 concerning Regulations for the Implementation of Law Number 6 of 2011 concerning Immigration and Minister of Law and Human Rights Regulation of the Republic of Indonesia Number 8 of 2014 concerning Passports Ordinary And Travel Letters Like Passports. Law enforcement against criminal offenses of Foreign Citizens to Indonesia without going through the examination of immigration officials then the perpetrators may be subject to administrative sanctions and criminal sanctions, the perpetrators who enter the territory of Indonesia without going through immigration officials have violated Article 113 of Law No. 6 of 2011 concerning immigration and sentenced to six months imprisonment